Companion to European Heritage Revivals - Egberts, Linde; Bosma, Koos.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Are you organising an international heritage project? Turning a so-called 'heritage revival' into a meaningful experience for the general public can be a challenge to historians, archaeologists, museum conservators and tourism professionals alike. This Companion to European Heritage Revivals offers inspiration and new ideas to those who want to engage a large, international audience in activities which bring the past to life. It offers a critical examination of the field’s basic concepts and discusses a vast array of 'heritage revival tools', including games, historical re-enactments, 3D-visualisations, films, television documentaries, spatial designs and, most importantly, international heritage routes. Through many case studies, this book demonstrates how various aspects of heritage can be effectively presented by linking historical places and landscapes in a single revival to create a multifaceted but coherent whole. Above all, it shows the exceptional success achieved by projects which consistently focus on creating meaningful experiences together with individual users.
PART I: THE CONTEXT: HERITAGE PRACTICES IN TODAY’S EUROPE -- Chapter 1: Experiencing the Past: Introduction to Experience, Strategies, Authenticity and Branding; Linde Egberts -- Chapter 2: Creating a Shared Past? Europe and the Frankish Heritage in One of its Heartlands: Alsace; Linde Egberts -- Chapter 3: Battlefield of Histories: Competition over Authenticity and Heritage in an Urban Region in Eastern Netherlands; Linde Egberts -- PART II: REVIVAL TOOLS -- Chapter 4: Strategies for a Heritage Revival in the Digital Age; Jasper Visser -- Chapter 5: Using Games to Mediate History; Connie Veugen -- Chapter 6: “This is Clearly Bullshit”: Some Views about History on Television; Mijke Pol -- Chapter 7: Lost Cities, Exotic Travel and Digging up the World: Historical Feature Films as a Means of Enhancing Appreciation of our Archaeological Heritage; Nina Schucker and Jan van Helt -- Chapter 8: When the Past Comes to Life: Historical Reenactment; Peter van der Plaetsen -- Chapter 9: Visualisation of Place and Landscape; Joske Houtkamp, Arnoud de Boer and Henk Kramer -- Chapter 10: From Preservation to Managing Change: Using Spatial Development as a Heritage Revival Tool; Felix van Veldhoven -- Chapter 11: Europe is a Journey: The European Cultural Route as an Instrument for Heritage Revival; Minke Walda -- PART III: CONCEPTS -- Chapter 12: Conceptual Fuel for Reviving the Past: Creating a Heritage Revival in Today's Europe; Linde Egberts.
Keywords: Cultural heritage; Management; Cultural Heritage; Cultural Management